Pro-environmental Behavior among Coffee Farmers in Muria Mountains Area - Makhali, Muhammad Niam; Widjanarko, Mochamad (Jurnal Ecopsy, 2023)
Environmental destruction due to unfriendly agricultural patterns is a major threat to human being. Human behavior types can endanger natural ecosystems such as forest encroachment, the use of chemical fertilizers, and illegal logging.  Unconsciously those cause natural disasters forlike flash floods, landslides, and soil contamination occurred. Based on the background research, the researcher took a sample of the behavior of coffee farmers in Muria mountains area. It is related by farming patterns has damage through the environmental preservation concept. Hence this study is aimed to analyze many factors that influence the pro-environmental behavior to coffee farmers in Muria mountains area. The research employed qualitative methods with a phenomenological approach. Data collection techniques in this study utilized interview and observation methods with the characteristics of the subjects as coffee farmers in the Muria Mountains region. While the data analysis applied coding. The credibility test of this study adopted a triangulation data source type. The results of this study indicate that there are several factors that affect coffee farmers in Muria Mountains area toward pro-environmental behavior such as motivation, yield, habits, costs, and knowledge of environmental sustainability. But there are yet coffee farmers who have no pro-environmental behavior. It is caused by considering various factors as well as have no will, lack of knowledge, complicate to find the dung, and fail the understanding of the environmental damage impact.